The Effectiveness of Footwork Exercises with the HIIT Method in Developing VO2max and Anaerobic Capacity - Donie Donie; Yanuar Kiram; Hermanzoni Hermanzoni; Eval Edmizal (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to determine the development of physiological aspects of increasing aerobic and anaerobic performance in students who become badminton athletes through optimizing footwork exercises using the high-intensity interval method (HITT). This research will provide a solution for trainers in combining and optimizing footwork exercises as a technique in badminton combined with the principles of interval training to increase badminton athletes' aerobic and anaerobic capacity. This study used an experimental approach by giving footwork training treatment (HITT) to 30 Padang State University students who became badminton athletes. Researchers saw the effect of the exercise given on aerobic capacity (VO2max) and anaerobic capacity. The statistical analysis results showed that footwork exercise with The HIIT (High High-Intensity Interval Training) method positively affects badminton athletes' maximal aerobic capacity (VO2max) anaerobic capacity. In this concept, footwork training using the HIIT method effectively develops aerobic and anaerobic metabolism in response to energy requirements during total energy production in training maximum.